2006
DOI: 10.1080/00986440500267261
|View full text |Cite
|
Sign up to set email alerts
|

Gas Dispersion and Solid Suspension in a Three-Phase Stirred Tank With Multiple Impellers

Abstract: Despite much research on gas-liquid-solid systems and their widespread application in industry, gas dispersion with solid suspension in multistage stirred reactors equipped with multiple impellers has received little attention. We report here the critical just-suspension impeller speed for different concentrations of solid particles, gas holdup, and shaft power in a vessel of 0.48 m diameter with four baffles and dished base. Five agitator configurations, each with three impellers mounted on a single shaft, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…The presence of solids will cause an increase in the emitted signal because of impacts of the particles with the wall, the impeller and with each other, but the system will be challenged to correctly predict the gas-liquid operating regime. The regime is considered unchanged at fixed air volumetric flow and impeller speed: for low concentration [< 20% w/w (Chapman et al 1983b)] of solids, works in the literature report little effects of the presence of the particles on the gas sparging dynamics (Bao et al 2006;Chapman et al 1983b).…”
Section: Sensing and Measurement Techniquesmentioning
confidence: 99%
“…The presence of solids will cause an increase in the emitted signal because of impacts of the particles with the wall, the impeller and with each other, but the system will be challenged to correctly predict the gas-liquid operating regime. The regime is considered unchanged at fixed air volumetric flow and impeller speed: for low concentration [< 20% w/w (Chapman et al 1983b)] of solids, works in the literature report little effects of the presence of the particles on the gas sparging dynamics (Bao et al 2006;Chapman et al 1983b).…”
Section: Sensing and Measurement Techniquesmentioning
confidence: 99%
“…Radial flow impellers resulted in a poor distribution of gas throughout the system even in multi‐impeller configurations such as a system with three Rushton turbines 15 . However, Bao et al 16 reported that a combination of a radial and an axial flow impeller resulted in a better gas distribution due to the radial impeller's high energy dissipation rate. Among radial impellers, the Scaba impeller has shown some promising characteristics in both single and multiphase systems as well as coaxial systems 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple authors also reported a small or no effect of the solid phase on the volumetric mass transfer coefficient 11–13. The increasing industrial importance of gas‐liquid‐solid systems has led to a focussed interest on the solid phase influence in such systems during the last couple of years 4, 14, 15. However, the mass transfer in gas‐liquid‐solid systems has not been fully described and understood, yet.…”
Section: Introductionmentioning
confidence: 99%